Numerical investigation into the effects of different initial imperfections on the lateral buckling of submarine pipelines. (1st January 2020) - Li, Chengfeng; Liu, Run
Abstract: Initial imperfections (out of straightness) constitute one of the key parameters impacting lateral buckling of pipelines as they influence both pre-buckling assessment and pipeline integrity assessment during the post-buckling stage. When adjacent imperfections exist in a submarine pipeline, the influence regularity of initial imperfections on the global buckling of pipelines will become more complicated. An elastic-plastic 3D-Explicit numerical method is proposed to investigate the global lateral buckling of pipelines with single and double imperfections. Then, an investigation is conducted on the influences of the spacing, relative direction and relative size of double imperfections on the global buckling characteristics, such as the critical temperature rise, the buckling deformation amplitude and the buckling mode. Based on the limit state criteria of global buckling pipelines in DNVGL-RP-F110, the structural integrity of pipeline with different buckling modes is assessment. The results show that pipeline failure has a certain correlation with its buckling mode type. For pipelines with the same buckling mode type, the pipeline failure parameter is approximately linearly associated with the double-imperfection spacing. Highlights: An elastic-plastic 3D-Explicit numerical method is proposed, which considers the plastic characteristics of pipelines post buckling. Types of buckling modes for double-imperfection pipelines are summarized. And the relationship between the failure parameter of pipelines and their buckling mode types is illustrated. Influence mechanism of the larger imperfection among double imperfections on the buckling of the smaller imperfection is illustrated.